INCOME (EARNINGS) INDEXATION OF ENTERPRISE EMPLOYEES: ACCOUNTING AND CONTROL - T. Melnik (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article defined income of employees subject to indexation considered method of calculating CPI for indexation features reflected in the accounting and reporting of amounts indexed income of employees, agents that carry out supervision and control of violation of labor laws regarding Ukraine of indexation, the types of businesses liable for violation of labor laws.